Synthesis and location of intracellular Tetraphenylporphyrin lipophilic in electrocytes of Psammobatisextenta - Prado Figueroa, María (2003)
We describe the synthesis of 5, 10, 15,20-tetra~s(4-n-dodec~phenyl) porphyrin and his intracellular localization in electrocytes of Psammobatis extenta (Rajidae). The localization was monitored by the observation of the rod fluorescence exhibi1ed by this porphyrin derivativa. This compound shows big afinitty for tl1e electromotor nerves and the nuclear chrornatin of electrocytes. Both structures exhibited intense fluorescence. Whereas, the mitochondna were slightly fluorescent. Additionally, the electron probe X·ray microanalysis suggests a migration of chloride and catíonic ions.